Bibliometrical analysis of workers quality on crowdsourcing based on VOS viewer - Cucus, Ahmad; B.A, Luhur; Al-Fahim, Mubarak Ali; Yuli Endra, Robby; Aprlinda, Yuthsi (2022)
Data collection activities are used for various needs in human life, such as business, education,health, transportation, and various other services. Data collection techniques through human assistance are also called crowdsourcing. Crowdsourcing is a distributed problem-solving mechanism that is available to the general public over the Internet. Crowdsourcing is one way to collect data and analyze data in big data. Some of the problems in collecting data from workers are as follows data received from workers have a high potential for noise because there has been no selection and validation on the quality of workers. However, it is not certain what factors can affect the quality of workers in crowdsourcing. This paper tries to explore the criteria that become the quality of workers in crowdsourcing activities by using Bibliometric Mapping by using tools such as VOS viewer.